Algebra-Gleichungen-Exponentialgleichungen


  • $a b^{(cx+d)}+f=0 $
    1 2 3 4 5 6
    $a e^{(cx+d)}+f=0 $
    1 2 3 4

Beispiel Nr: 03
$ \text{Gegeben:}a b^{(cx+d)}+f=0 \\ \text{Basis: }b \\ \\ \text{Gesucht:} \text{Lösung der Gleichung} \\ \\ a b^{(cx+d)}+f=0 \\ \textbf{Gegeben:} \\ a=5 \qquad b=4 \qquad c=2 \qquad d=1 \qquad f=-10 \\ \\ \textbf{Rechnung:} \\ 5 \cdot 4^{(2x+1)}-10 =0 \\ 5 \cdot 4^{(2x+1)}-10=0 \qquad /+10 \\ 5 \cdot 4^{(2x+1)}=+10 \qquad /:5 \\ 4^{(2x+1)}=2 \qquad /\log_4 \\ 2x+1=\log_4 \left(2 \right) \qquad / -1 \qquad / :2 \\ x=-\frac{1}{4} $